Mapping the dissociative ionization dynamics of molecular nitrogen with attosecond resolution. (August 2015) - Klinker, M; Trabattoni, A; González-Vázquez, J; Liu, C; Sansone, G; Linguerri, R; Hochlaf, M; Klei, J; Vrakking, M J J; Martin, F; Nisoli, M; Calegari, F
Synopsis: We wish to understand the processes underlying the ionization dynamics of N2 as experimentally induced and studied by recording the kinetic energy release (KER) in a XUV-pump/IR-probe setup. To this end a theoretical model was developed describing the ionization process using Dyson Orbitals and, subsequently, the dissociation process using a large set of diabatic potential energy surfaces (PES) on which to propagate. From said set of PES, a small subset is extracted allowing for the identification of one and two photon processes chiefly responsible for the experimentally observed features.